An Incomes policy for Britain : policy proposals and research needs - Blackaby, Frank Thomas; National Institute of Economic and Social Research; Social Science Research Council (Great Britain) (London : Heinemann Educational, 1972)
Income policy is a wide ranging subject, not just a technical economic device. It ramifies into questions such as income distribution and the relationship between trade unions and the state. Thus the need for this book.
"Report of a conference held in London in January 1972."
Includes index.
Includes bibliographical references: p. 237-243.
occ 16/01/2019
Loans
Keywords: Wage--Price policy; Great Britain